Revision of the genus Dicranopalpus from northern Spain and Corsica, with descriptions of two new species (Arachnida, Opiliones, Phalangioidea) - Wijnhoven, Hay; Martens, Jochen; Prieto, Carlos E. (European Journal of Taxonomy, 2022)
The Iberian Peninsula represents a diversity hotspot for the genus Dicranopalpus. However, most taxa are insufficiently defined. Our revision of the Dicranopalpus pyrenaeus species group reveals two hidden species: D. catariegensis sp. nov. and D. gallaecicus sp. nov. Two species, D. pyrenaeus from the Spanish and French Pyrenees and D. insignipalpis from Corsica, are redescribed. Dicranopalpus cantabricus Dresco, 1953 is resurrected as a valid species. Three new synonyms of D. martini (Simon, 1878) are proposed: Fagea bolivari Dresco, 1949 (including D. bolivari sensu Rambla 1975), Egaenasser extraordinarius Roewer, 1953 and Dicranopalpus dispar Rambla, 1967. With these additions, the Iberian Peninsula harbours four species of the Dicranopalpus pyrenaeus species group. They largely have allopatric distributions, ranging from the Pyrenees and the Cantabrian mountain range to the west coast of Galicia.